2021
DOI: 10.3389/fphar.2021.702529
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Oleanolic Acid as Allosteric Agonist of Integrin αM by Combination of In Silico Modeling and In Vitro Analysis

Abstract: Oleanolic acid is a widely distributed natural product, which possesses promising antitumor, antiviral, antihyperlipidemic, and anti-inflammatory activities. A heterodimeric complex formed by integrin αM (CD11b) and integrin β2 (CD18) is highly expressed on monocytes and macrophages. In the current study, we demonstrate that the I domain of αM (αM-I domain) might present a potential cellular target for oleanolic acid. In vitro data show that oleanolic acid induces clustering of αM on macrophages and reduces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Indeed, SEED analysis of the respective integrin α I domains revealed that allosteric modulation by small molecules may be possible through these pockets. For Mac-1, this finding is in agreement with earlier molecular docking studies referred to above. For VLA-1 the current study is the first study to suggest that this integrin may be targetable via the β 6 –α 7 pocket. Although VLA-1 is a promising therapeutic target, pharmacological progress in designing VLA-1 inhibitors has been slow, to date.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, SEED analysis of the respective integrin α I domains revealed that allosteric modulation by small molecules may be possible through these pockets. For Mac-1, this finding is in agreement with earlier molecular docking studies referred to above. For VLA-1 the current study is the first study to suggest that this integrin may be targetable via the β 6 –α 7 pocket. Although VLA-1 is a promising therapeutic target, pharmacological progress in designing VLA-1 inhibitors has been slow, to date.…”
Section: Discussionsupporting
confidence: 92%
“…Despite this promise, no rigorous attempts have been made to date towards identifying molecules targeting putative α I allosteric sites similar to the LFA-1 α I allosteric site in other integrins. A few in silico studies provide evidence that such sites may exist in integrins closely related to LFA-1, e.g., αxβ 2 (CD11c/CD18) and Mac-1. In addition, there is evidence suggesting that the putative α I allosteric site of Mac-1 can accommodate inhibitors as well as activators , of Mac-1 function. However, these investigations did not prompt further research into the accessibility and druggability of putative α I allosteric pockets in other integrins.…”
Section: Discussionmentioning
confidence: 99%